Limitations of multiprofessional work: a case study of STD/AIDS reference centers - Silva, Neide Emy Kurokawa e; Oliveira, Luzia Aparecida; Figueiredo, Wagner dos Santos; Landroni, Maria Angela da Silva; Waldman, Chang Chung Sing; Ayres, José Ricardo CM (Revista de Saúde Pública, 2002)
OBJECTIVE: To understand the possibilities and limitations of developing coordinated work among professionals of different background in order to promote work collaboration and improve the quality of care of HIV/AIDS patients. METHODS: A qualitative study on multiprofessional work was carried out in five STD/AIDS reference centers in the city of São Paulo, Brazil. Semi-structured interviews were applied to 26 professionals from different background, focusing on how they position their practices in a multiprofessional setting. RESULTS: Significant differences were observed as to the outreach of multiprofessional work collaboration and possibilities of improving health care are related to the circumstances the multiprofessional work is done. CONCLUSIONS: When the multiprofessional team has to deal with predictable circumstances and the planning of long-term care projects where demands are anticipated from situations found in their practices, this creates better working conditions for effective collaboration. This collaboration favors interventions that promote a more productive interaction between the medical treatment and other relevant dimensions of care, such as social, psychological, and emotional needs of the patients.